Giant left‐sided inguinoscrotal hernia containing the cecum and appendix (giant left‐sided Amyand's hernia). Issue 6 (10th October 2014) - Maeda, Kenichi; Kunieda, Katsuyuki; Kawai, Masahiko; Nagao, Narutoshi; Tanaka, Chihiro; Oida, Yasuhisa; Kiyama, Shigeru; Tawada, Masahiro
Key Clinical Message The present case involved a 62‐year‐old male with a large left‐sided inguinoscrotal hernia. A CT scan and a clinical examination led to a diagnosis of a giant left‐sided Amyand's hernia. The hernia was repaired using the ULTRAPRO Hernia System (UHS), and the patient exhibited an uneventful postoperative course.